Effect of feeding diets containing barley, wheat and corn distillers dried grains with solubles on carcass traits and meat quality in growing rabbits - Alagon, Gilbert; Arce, Orlando; Serrano, Paula; Ródenas, Luis; Martínez-Paredes, Eugenio; Cervera, Concepcion; Pascual, Juan J.; Pascual, Mariam (2017)
The effect of dietary inclusion of distillers dried grains with solubles (DDGS) on carcass and meat quality of longissimus muscle was studied in 100 growing rabbits from 28 to 59 days old. Diets with no DDGS (C), barley (Db20), wheat (Dw20) and corn (Dc20) DDGS at 20% and corn (Dc40) DDGS at 40% were formulated. No effects on most of the carcass traits, texture and water holding capacity were found. Barley and corn DDGS led to a higher dissectible fat percentage. Meat redness was higher with Dw20 and pH was higher with Dw20 and Db20 than with Dc20. Protein and saturated fatty acids concentration declined as corn DOGS level increased. Dc40 led to the lowest saturated/unsaturated fatty add ratio, atherogenic index and thrombogenic index. In conclusion, dietary inclusion of these DDGS at 20% did not affect most of the carcass and meat quality traits in rabbits.